PERAN GURU DALAM MEMBERIKAN PELAJARAN TAMBAHAN (LES) BAGI PESERTA DIDIK DI LUAR JAM PELAJARAN SEKOLAH SEBAGAI WUJUD IMPLEMENTASI PENGABDIAN KEPADA MASYARAKAT - Oktaviani Dwi Saputri; Rahmawati Rahmawati (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
Writing this article aims to determine the role of teachers in providing additional lessons (tutoring) for students outside school hours as a manifestation of the implementation of community service. The teacher is seen as a person who is responsible for the success or failure of learning activities towards changes in behavior of each individual, both in terms of providing motivation, fostering moral values and also as a controller for each student he teaches. According to parents of students, teachers are deemed necessary to provide additional lessons informally outside of school hours to students, given the limited time at school often results in students not understanding each subject matter they receive. Therefore the existence of teachers and the willingness of teachers to take the time to provide additional lessons is very helpful for students to better understand and prepare students in the learning process. The role of the teacher in the community is not only at the time of teaching hours in school, but in all aspects of the life of the teacher will be a role model and a real example for students and has a positive impact on the environment where he lives